The Influence of Technology Acceptance Model (TAM) Theory on Intention to Reuse Mobile Banking with Customer Satisfaction as Intervening Variable (Case Study of BRIMO Application in Workers PT. Bank Rakyat Indonesia Kantor Wilayah Surabaya) - Zuhrotus Sholihah Zain; Timotius Febry Christian (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study examines the effect of the technology acceptance model (tam) on the intention to reuse mobile banking with customer satisfaction as an intervening variable (a case study of the BRIMo application on employees of PT Bank Rakyat Indonesia Surabaya Regional Office), using the purposive sampling method with a total sample of 140 workers from various fields division in PT Bank Rakyat Indonesia (Persero) Tbk regional office Surabaya. The data analysis technique used structural equation modelling (SEM) analysis with the help of the Smart PLS 4 program. The findings show that the elements of the technology acceptance model (tam) theory of perceived usefulness and perceived ease of use have an influence on customer satisfaction, and perceived usefulness, perceived ease of use, customer satisfaction have an influence on intention to reuse in accordance with the hypothesis built in the study. In this study, customer satisfaction has no influence as an intervening variable between perceived ease of use and intention to reuse. The implication of this research is that PT Bank Rakyat Indonesia continues to pay attention to the BRImo application, always providing convenience and comfort for users. The company also pays attention to the reviews given by BRImo users, through good reviews it will have a good impact on the company.